Transeustachian Middle Ear Endoscopy Using a Steerable Distal-Camera Tipped Endoscope. Issue 2 (20th October 2021) - Freeman, Michael H.; Gafford, Joshua B.; Fichera, Loris; Noble, Jack; Webster, Robert J.; Labadie, Robert F.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Demonstrate the ability of a novel steerable distal chip endoscope to traverse the Eustachian tube and provide diagnostic quality images of the human middle ear. Patients: Three cadaveric temporal bone specimens were used in this work. Intervention: Diagnostic transeustachian endoscopy of the middle ear was performed. Main Outcome Measure: Diagnostic image quality. Results: A novel 1.62 mm steerable endoscope successfully cannulated the Eustachian tube of three human cadaveric temporal bone specimens to reveal intact middle ear anatomy with high optical clarity. Conclusions: A steerable endoscope can be designed to traverse the human Eustachian tube and provide diagnostic quality images of middle ear anatomy.